Leadership Through Example: Reconstructing the Timothy Model for Fostering Spiritual Maturity in Generation Z at GBI Light of City - Raphael Christopher; Kornelius Rulli Jonathans; Andreas Eko Nugroho (Sekolah Tinggi Teologi Transformasi Indonesia, 2026)
This study aims to examine whether Timothy’s leadership style—specifically the role of a role model as described in 1 Timothy 4:12—can influence the spiritual development of Generation Z (Gen-Z) at the GBI Light of City (LoC) church. As we approach an era in which the majority of the productive generation will retire, Gen-Z must be prepared as future leaders. However, challenges such as skepticism toward traditional authority, spiritual vulnerability, and the influence of digital technology pose major obstacles to their spiritual maturity. This study aims to identify leadership factors relevant to Gen-Z’s values and provide practical insights to enhance church programs targeting their spiritual growth. Using a qualitative approach with text analysis, this study found that Timothy’s leadership qualities—such as authenticity, integrity, unconditional love, steadfast faith, and moral purity—resonate strongly with Gen-Z’s values. The results highlight the importance of the role of the pastor, exemplary leadership, and the use of technology in supporting the spiritual formation of Gen-Z. A novel contribution of this study is that Timothy’s leadership model can be effectively adapted to meet the spiritual needs of Gen-Z in the modern era.